2020
DOI: 10.13189/saj.2020.080620
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Balance Learning in Primary School Students

Abstract: Balance is the ability to react to any change in body position so that the body remains stable and in control. A right balance will enable a person to carry out activities and movements effectively and efficiently with minimal risk of falling. A balanced training program is given as many athletes get injured during peak periods and training for patients with Multiple Sclerosis and Down Syndrome. The author is interested in proving and implementing various forms of balance training applied to children who parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…This evaluation predicts the range of motion, proprioception, and muscle strength of the weight-bearing. Because leg muscles and nerves are efficiently controlled so that the axis of movement and balance can be maintained at the base of support in the single foot support posture [29][30]. It helps to do.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This evaluation predicts the range of motion, proprioception, and muscle strength of the weight-bearing. Because leg muscles and nerves are efficiently controlled so that the axis of movement and balance can be maintained at the base of support in the single foot support posture [29][30]. It helps to do.…”
Section: Assessmentmentioning
confidence: 99%
“…It helps to do. Gribble [31] reported that this scale showed high validity and test-retest reliability. (ICC = 0.96).…”
Section: Assessmentmentioning
confidence: 99%
“…This phenomenon is not sufficient for physical activity. Therefore, children need to be given simulations or examples in each activity [6]. Thus, we need media that can assist in training activities and be well-used in every physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by references [12], [13] the level of endurance is fundamental and by the needs of the referee who is constantly faced with modern matches or fast-paced games, because when the endurance increases, he will have the strength and endurance to carry out the task of leading the match without experiencing significant fatigue. As explained in the volleyball rules, there are several hand signals for the referee, and the referee must be able to apply according to the field's mistakes.…”
Section: Introductionmentioning
confidence: 99%